Wavell in the Middle East, 1939-1941 : A Study in Generalship - Raugh, Harold E. (London Brassery's (UK), 1993)
This masterly study of generalship covers two years of intense operational activity during which Field Marshal Wavell, as Commander-in-Chief, Middle East, was at one point conducting no fewer than five campaigns simultaneously. Two of those campaigns will stand in history as truly great victories, and one$1 (Bthe campaign in Greece in 1941$1 (Bas a source of endless controversy.s
Include Pictures, Maps, Notes and Index
Foreword by Field Marshal The Rt. Hon. Lord Carver GCB CBE DCO MC
Keywords: World War (1939-1945) -- Africa, North -- Middle East -- Military Campaigns